Conception of freedom in Friedrich Nietzsche’s philosophy - Dżugaj, Marcin (Hybris, 2022)
The article presents the conception of freedom in Nietzsche's thought in the three periods of his writings. In the first period Nietzsche believe that freedom is connected with estethical-tragic contempletion in the Greek tragedy. He also points out that freedom is culture-forming act in the unity with oneself and with the world. In the second period Nietzsche says that to become truly free is to liberate oneself from the metaphysics and religious tradition. In the third period Nietzsche is convinced that only those who have gived themselves the law which is an expression of their nature are truly free.